Marketing Communication: Peran Guerrilla Marketing Terhadap Keputusan Pembelian Di Eropa - Gita Cahyani (Lembaga Pengembangan Kinerja Dosen, 2023)
Guerrilla marketing is a marketing strategy that was developed in the early 1980s by Jay Conrad Levinson. The idea behind guerrilla marketing is to use unconventional and low-cost tactics to promote a brand or product. This study aims to describe the implementation of guerrilla marketing in Europe and describe the impact of guerrilla marketing on purchasing retention. The method used in this study is the literature review research method which provides output to existing data, as well as an elaboration of a finding so that it can be used as an example for research studies in compiling or making a clear discussion of the contents of the problem to be studied. Based on the research results, it can be seen that it is an innovative marketing strategy that has gained popularity in Europe. This low-cost method can be very effective in promoting a brand or product. Guerrilla marketing can have a significant impact on consumer purchasing decisions. Its unconventional and creative approach can create memorable experiences for consumers, leading to emotional connections with brands and influencing purchase decisions.